2019
DOI: 10.1155/2019/6402947
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Prevention Measures among Pregnant Women: A Population-Based Survey in Nnewi, Nigeria

Abstract: We examined factors related to the uptake of two malaria prevention measures, insecticide-treated bed-nets and prophylactic sulphadoxine-pyrimethamine (SP), among pregnant women in Nnewi, Nigeria. The survey had a quantitative and qualitative part. For each part, the subjects meeting our inclusion criteria were systematically identified in a population-based manner. For the qualitative part, focused group discussions, in-depth interviews with a wide variety of stakeholders (e.g., health workers, males whose wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…Similar to Bhalla et al study, educational level of pregnant women was associated with malaria preventive measures, but economic status and knowledge were not associated with preventive measures [33]. Furthermore, in this present study, those with tertiary educational levels were 6.8 times more likely to practice malaria prevention as compared to those without education.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to Bhalla et al study, educational level of pregnant women was associated with malaria preventive measures, but economic status and knowledge were not associated with preventive measures [33]. Furthermore, in this present study, those with tertiary educational levels were 6.8 times more likely to practice malaria prevention as compared to those without education.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the use of long-lasting insecticidal nets significantly decreased the risk of occurrence of the first malaria infection in early pregnancy in a study that assessed the use and effectiveness of long-lasting insecticidal nets in early pregnancy in Benin and its impact on malaria infection risk [25]. This finding supports reports that the use of ITNs substantially reduced the risk of malaria in pregnancy and, therefore, was a protective factor against developing malaria in pregnancy [26][27][28][29].…”
Section: Discussionsupporting
confidence: 78%
“…Data from the 2012 DHS revealed that marital status and relationship with the head of household were significantly associated with MPMs use. Indeed, married women were more likely to use MPMs during pregnancy than single women, who require special attention because they can remain hidden and resort to self-medication [ 31 ]. In fact, in Nigeria, women reported needing the support or consent of their husbands before going to an ANC or taking the medication [ 28 ].…”
Section: Discussionmentioning
confidence: 99%